Mechanistic Investigation of the Counterion-Induced UCST Behavior of Poly(N, N-dimethylaminoethyl methacrylate) Polymer Brushes - Flemming, Patricia; Mueller, Martin; Fery, Andreas; Muench, Alexander S.; Uhlmann, Petra (Macromolecules, 2020)
Because of its multiresponsive behavior upon variation of pH value, temperature, and ionic strength, poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA) is an attractive candidate for adaptive surface coatings, especially in the field of biomedical sensors. In the presented article, PDMAEMA Guiselin brushes (5-12 nm, dry thickness) were prepared by the grafting-to approach, and the thermoresponsive UCST-type (upper critical solution temperature) behavior of the generated films, induced by [Fe(CN)6]3-, was demonstrated for the first time. To clarify the specific mechanism of the temperature responsiveness, the molecular interactions between polymer chains and complex ions were studied by in situ infrared spectroscopy and in situ ellipsometry, showing wavenumber shifts of the ν(CN) band due to ion pairing as well as changes of the ν(OH) band intensity due to swelling. Conclusively, experimental data suggest that the electrostatic interaction between the two components plays a significant role in the thermoresponsive behavior of PDMAEMA films. Using this knowledge, the UCST of the PDMAEMA Guiselin brushes could be adjusted between 34.0 ± 1.2 °C at pH 8 and 40.7 ± 2.0 °C at pH 5.
CRIS-Team Scopus Importer:2022-04-14